Gulen's thoughts on promoting mutual respect and better understanding among multi-religious communities through inter-religious dialogue - Shehu, Fatmir Mehdi (2011)
This paper will examine Gülen's inspiring thoughts on the necessity of inter-religious dialogue through which mutual respect and better understanding among multi-religious communities can be promoted. Due to the lack of mutual respect and better understanding of one another, the followers of multi-religious communities have experienced a relationship prevailed by one's enmity, superiority, selfishness, and disrespect for others. Indeed, this very hostile environment has been an immense obstacle for the construction of a friendly coexistence among the followers of world religions in general and the followers of Islam and Christianity in particular. According to the Holy Qur'an, Allah (s.w.t.) has revealed to humanity only one Transcendental Way of Life - DÊn al-IslÉm (complete submission and obedience to the Creator). Nevertheless, compulsion of people to this way of life is forbidden. Islam, hence, encourages Muslims to enter into a dialogue with others. The Islamic approach towards inter-religious dialogue has inspired many scholars of religion in general and Fethullah Gülen, a contemporary Muslim thinker, in particular to assert that mutual respect and better understanding among the members of multi-religious communities can be promoted through sincere dialogue only. Gülen's starting point for dialogue is Islam, which is a religion of peace and dialogue. According to Gülen, the Holy Qur’an promotes the fundamental pillars of dialogue, like tolerance, forgiveness, humility, mutual respect, and better understanding. For Gülen, to have a fruitful inter-religious dialogue between Muslims and others, an intra-dialogue must first start amongst Muslims. Dialogue can take place in different aspects of peoples’ daily activities, like religious, civilizational, political, sociological, cultural, economic, and so on. After a philosophical analysis of Gulen's thoughts on inter-religious dialogue, this study strongly assures to provide important solutions, which will help Muslim and Christian communities of Nigeria to enhance their relationships. Finally, this paper will provide for the conference audience an awareness of accepting each other as they are and not as they want each other to be.